Is There any Diwali Effect? - Kumar, Umesh (Indian Journal of Finance, 2012)
This study investigates the existence of seasonality in National Stock Exchange. The study uses the monthly return data of the S&P CNX NIFTY Index. After examining the stationary of the returns series, the researcher used Paired T-test in order to check excess returns before 8 days (inclusive of Mahurat trading day) and after 7 days. The researcher also checked out of the sample data for 15 days and 20 days for checking the existence of excess return and came out with same results. Further, the researcher used EGarch model for checking the volatility of index during 15 days prior and post Mahurat Trading day (excluding Mahurat trading day). The study reveals evidence of excess returns during the period of 7 days post Mahurat Trading and greater volatility during the period of post Mahurat trading day as compared to pre Mahurat trading day. The evidence of seasonality implies that the National stock exchange market is not informationally efficient. Hence, investors may be able to time their share investments to improve returns.